Rapid spontaneous regression of a lumbar juxta-facet cyst - Ucler, Necati; Ozturk, Sait; Gulkesen, Arif; Kaplan, Metin (Medknow Publications & Media Pvt Ltd, 2017)
[Abstract Not Available]
Keywords: Synovial Cysts